2019
DOI: 10.1016/j.jaap.2019.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of H2S on the thermal cracking of alkylbenzenes at high pressure (70 MPa) and moderate temperature (583–623 K)

Abstract: The main products are toluene, ethylbenzene, iso-butylbenzene and hydrocarbon gases (C 1 , C 2 and C 3).  Several organosulfur compounds are produced: mainly short thiols, phenylbutanethiols, and phenylthiophenes.  H 2 S accelerates the pyrolysis of n-butylbenzene by a factor up to almost 4 depending on the experimental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Vitzthum et al determined that the pyrolysis rate of n -butylbenzene accelerated under high-pressure conditions during the pyrolysis of H 2 S with n -butylbenzene. 24 The apparent activation energy of the pyrolysis of n -butylbenzene decreased from 66.6 kcal mol −1 (pure n -butylbenzene) to 55.9 kcal mol −1 ( n -butylbenzene in a mixture with H 2 S). Nguyen et al reported on the pyrolysis properties of a mixture of n -octane and H 2 S. Many types of thiols and heavy hydrocarbons were formed in the presence of H 2 S, owing to the progress of the reaction between the hydrocarbon molecules and the radicals produced from H 2 S. 25 Zeng et al investigated the interaction of sulfanyl radicals (SH*) with aliphatic (C1–C4) hydrocarbons via calculations using CBS-QB3.…”
Section: Introductionmentioning
confidence: 97%
“…Vitzthum et al determined that the pyrolysis rate of n -butylbenzene accelerated under high-pressure conditions during the pyrolysis of H 2 S with n -butylbenzene. 24 The apparent activation energy of the pyrolysis of n -butylbenzene decreased from 66.6 kcal mol −1 (pure n -butylbenzene) to 55.9 kcal mol −1 ( n -butylbenzene in a mixture with H 2 S). Nguyen et al reported on the pyrolysis properties of a mixture of n -octane and H 2 S. Many types of thiols and heavy hydrocarbons were formed in the presence of H 2 S, owing to the progress of the reaction between the hydrocarbon molecules and the radicals produced from H 2 S. 25 Zeng et al investigated the interaction of sulfanyl radicals (SH*) with aliphatic (C1–C4) hydrocarbons via calculations using CBS-QB3.…”
Section: Introductionmentioning
confidence: 97%